Base-promoted anaerobic intramolecular cyclization synthesis of 4, 5-disubstituted-1, 2, 3-thiadiazoles. Issue 10 (5th April 2022) - Dong, Cong; Mai, Shaoyu; Wang, Shuai; Li, Xin; Song, Qiuling
Abstract : An alkali-promoted, transition-metal-free and oxidant-free method to construct 4, 5-disubstituted-1, 2, 3-thiadiazoles from N -tosylhydrazone-bearing thiocarbamates by employing a sustainable intramolecular reaction strategy has been developed. Abstract : An alkali-promoted, transition-metal-free and oxidant-free method to construct 4, 5-disubstituted-1, 2, 3-thiadiazoles from N -tosylhydrazone-bearing thiocarbamates by employing a sustainable intramolecular reaction strategy has been developed. This reaction features high efficiency and good functional group compatibility, readily available starting materials and valuable products. Furthermore, this method has great potential in the synthesis of natural products, pharmaceuticals and materials.